PENGARUH PENDAPATAN DAN SUKU BUNGA TERHADAP KEPUTUSAN PENGAMBILAN KPR PADA PT BANK TABUNGAN NEGARA (PERSERO) TBK CABANG PRABUMULIH - Emi Sukmawati (Islamic Banking : Jurnal Pemikiran dan Pengembangan Perbankan Syariah, 2020)
This study is entitled "The Effect of Income and Interest Rates on the Decision of Taking Mortgages at PT Bank Tabungan Negara (Persero) Tbk Prabumulih Branch". The main problem in this research is how much income and interest rates influence the decision to take KPR at PT Bank Tabungan Negara (Persero) Tbk Prabumulih Branch. Determination of the sample in this study is to use the accidental sampling method, namely random sampling. The number of samples studied were 100 respondents who worked, both as private employees, BUMN employees, and Civil Servants (PNS) who were classified based on the income they received per month. The analytical method used is multiple linear regression with hypothesis testing using the F test, t test, and the coefficient of determination (R2). The results of this study concluded that income and interest rates influence the decision to take a mortgage at PT. Bank Tabungan Negara (Persero) Tbk Branch Prabumulih of 46.8%. Researchers give advice, companies engaged in housing should really pay attention to what factors are very influential in determining the buyer's decision to take a mortgage so that companies avoid unwanted problems, such as bad loans